THE EFFECT OF UNDERSTANDING TAX REGULATIONS, THE FIRMNESS OF TAX SANCTIONS, AND THE EASE OF TAX APPLICATIONS ON VILLAGE GOVERNMENT TAX COMPLIANCE - saputra, ngurah paramartha mahottama saputra; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2025)
This study aims to analyse the effect of understanding tax regulations, the firmness of tax sanctions, and the ease of tax applications on village government tax compliance. This type of research is quantitative research using a Likert scale questionnaire method, and the data results are processed using SPSS version 25. The population in this study consisted of all village governments in Buleleng Regency, comprising 129 villages. Then the sample used was total, namely all village finance clerks/treasurers in Buleleng Regency. The research data analysis used descriptive statistical analysis, data quality tests, classical assumption tests, and hypothesis testing. The results of this study indicate that understanding tax, the firmness of tax, and the ease of taxation applications and sanctions have a positive effect on village government tax compliance